Responding to intimate partner violence: Healthcare providers' current practices and views on integrating a safety decision aid into primary care settings - Alvarez, Carmen; Debnam, Katrina; Clough, Amber; Alexander, Kamila; Glass, Nancy E. (Research in nursing & health, 2018)
ABSTRACT Supportive care for survivors of intimate partner violence (IPV) remains limited in primary care settings. Low‐income and Spanish‐speaking survivors of IPV are even more disadvantaged, given the dearth of linguistically and culturally appropriate interventions for IPV. We conducted semi‐structured individual interviews with 17 healthcare workers, including physicians, nurses, and social workers, to describe how healthcare workers serving primarily low‐income, Latina populations are currently screening and responding to IPV disclosure, and to explore the acceptability of integrating an interactive, personalized safety decision aid application—myPlan app—into the clinic setting. Despite recognition of IPV as a problem, none of the clinical sites had a protocol to guide screening and response to IPV disclosure. Screening practices varied across the sites, sometimes conducted by medical assistants prior to the provider visit and other times by the physician or nurse provider. When IPV was disclosed, it was often during assessment for a presenting problem such as poor sleep or anxiety. Most healthcare workers felt that clinical and community resources were limited for their patients experiencing IPV. The “warm hand‐off” to a social worker was the most common response strategy when possible; otherwise, women were given information about available resources such as hotlines and safe houses. We discuss structural, family, and individual barriers to accessing safety resources for underserved women and review how an easily accessible safety decision app, such as myPlan, could be a resource for women to safely tailor an action plan for her situation.